Application of Periodogram-Based Cointegration Test for the Analysis of the Services and Goods Sector Inflations - Yilmaz Akdi; Koray Kalafatcilar; Kivilcim Metin-Ozcan (International Econometric Review (IER), 2010)
The differing dynamics of the inflations of the services and goods sectors has been of major concern in Turkey. The persistence of the services sector inflation during disinflation periods hampered the efforts of the Central Bank of Turkey of hitting inflation targets in a country with long-lasting high inflation experience. In search of a possible long-run relationship between the services and goods sectors' inflations, this paper employs a method based on periodograms of the series in addition to time series tools. A periodogram-based test has pros over conventional tests; this test is model-free, seasonally robust and mean invariant. Empirical findings obtained from the methods employed in this study, Engle-Granger's and Johansen's conventional long-run time series tools as well as periodogram based test, suggest that services and goods sector inflations in Turkey are not cointegrated.
Keywords: E31; E58; C13; 330; Cointegration; Periodogram; Time-Series Analysis; Inflation; Services Sector